A new Anurida species of the hammerae-group from the Russian Far East (Collembola, Neanuridae) - Babenko, Anatoly; Nakamori, Taizo (Zootaxa, 2021)
A new species of the genus Anurida is described and illustrated based on material from the Khabarovsk Territory, Russia: A. hirsuta sp. nov. This new species belongs to the amphi-Pacific hammerae-group and it seems to be particularly similar to the Beringian A. hammerae Christiansen, 1952 and the Japanese A. trioculata Kinoshita, 1916. Anurida hirsuta sp. nov. can easily be distinguished from both latter species primarily by its peculiar dorsal chaetotaxy, apparently the most complete among all congeners. A key is presented to all eight species presently known to compose the group.